Effects of rutin supplementation on intestinal morphology, antioxidant capacity, immunity, and gut microbiota of laying hens fed a diet containing stored soybean meal - Hengzhi Li; Rui Jin; Yunfeng Gu; Yanmin Zhou (Italian Journal of Animal Science)
Protein oxidation of soybean meal (SBM) during storage may have adverse effects on the intestinal health of laying hens. Moreover, rutin has anti-inflammatory and antioxidant properties which might be used as a feed additive to mitigate the intestinal damage caused by oxidised protein of SBM. This study aimed to investigate the effects of rutin supplementation on intestinal morphology, antioxidant capacity, immunity and caecal microbiota in laying hens fed a diet containing stored SBM. A total of 384 Hy-Line Brown laying hens (220 days) were randomly allocated into four groups with eight replicates of 12 laying hens each according to a 2 × 2 factorial arrangement with 2 types of SBM (FSM: SBM was stored in the cold storage warehouses at −20 °C for 45 days, and was considered as fresh and control SBM; RTSM: SBM was stored in room temperature warehouse (15 °C to 25 °C), average temperature was 20 °C for 45 days) and 2 levels of rutin (0 and 500 mg/kg). The results showed that the RTSM diet decreased the ileal glutathione peroxidase (GSH-Px) activity, the jejunal superoxide dismutase 2 (SOD2) and ileal NAD(P)H: quinone oxidoreductase 1 (NQO1) mRNA expression levels (p < 0.05), and tended to decrease the jejunal superoxide dismutase 1 (SOD1), ileal glutathione peroxidase 1 (GPX1) and increase the jejunal interleukin-1β (IL-1β) and interleukin-4 (IL-4) mRNA expression levels. Dietary rutin decreased the jejunal crypt depth (CD) (p < 0.05), increased the jejunal total antioxidant capacity (T-AOC) and GSH-Px activities (p < 0.05), decreased the content of interferon-γ (IFN-γ) in the jejunum (p < 0.05), and significantly reduced levels of immunoglobulin G (IgG), IL-1β, tumour necrosis factor-α (TNF-α), IFN-γ, and IL-4 in the ileal mucosa (p < 0.05). Dietary rutin increased SOD2, nuclear factor E2-related factor 2 (Nrf2) and NQO1 mRNA expression levels in the jejunum and GPX1, Nrf2 and NQO1 mRNA expression levels in the ileum, and decreased nuclear factor-κB (NF-κB), IL-1β, IFN-γ and IL-4 mRNA expression in the jejunum and NF-κB, IL-1β, TNF-α, IFN-γ and IL-4 mRNA expressions in the ileum. What’s more, dietary rutin changed the caecal microbiota. PCoA analysis indicated significant structural differences among four groups (p < 0.05), and SBM × Rutin interactions were found in Actinobacteriota and unclassifiedk_norank_d_ Bacteria at the phylum level (p < 0.05). These results suggested that RTSM had slight adverse effects on the intestinal health, and dietary rutin improved intestinal morphology, exerted antioxidant and anti-inflammatory effects via Nrf2 and NF-κB signal pathways, and changed the composition of caecal microbiota.Highlights The RTSM diet has adverse effects on the intestinal health of laying hens compared with the FSM diet. Dietary rutin improved the intestinal health by increasing the intestinal morphology, antioxidant capacity and anti-inflammatory effects. Dietary soybean meal and rutin changed the composition of caecal microbiota.